The effect of the combination of acupressure therapy and breast care on the duration of smooth breastfeeding in postpartum women in the PMB working area of Pujokerto Trimurjo health center, Central Lampung - Rahmawati, Mega; Lestari, Ima (Jurnal Kesehatan Metro Sai Wawai, 2024)
Introduciton: Insufficient breast milk is one of the main obstacles to the success of exclusive breastfeeding. Data from the Pujokerto Health Center work area shows that 61% of postpartum mothers experience insufficient breast milk. Objective: The study aims to determine the effect of a combination of acupressure and breast care therapy on the duration of smooth breast milk in postpartum mothers. Method: Quantitative research with a quasi-experimental pretest-posttest group design. The sample consisted of 14 respondents, divided into two groups: intervention (acupressure + breast care) and control (only breast care). Data analysis used the dependent T test. Results: The average number of days of smooth breast milk in the intervention group was 3.14 days and the control group was 3.42 days. The bivariate test showed a p-value = 0.414 (≥ 0.05), meaning that there was no significant effect between the combination of therapies on the duration of smooth breast milk. Conclusion: There was no significant effect of the combination of therapies on the duration of smooth breast milk.